Pengaruh Cooperative Meaningful Instructional Design (C-MID) Berbantuan Multimedia Interaktif Terhadap Penguasaan Konsep Fisika Peserta Didik - Al Qoni'ah; Hairunnisyah Sahidu; I Wayan Gunada (Department of Physics Education, Universitas Mataram, 2020)
This research aimed to examine the effect of cooperative meaningful instructional design assisted interactive multimedia for studentsÃ¢â¬â¢ physics concept mastery. This type of research was quasi experiment with untreated control group designed by pretest and posttest.The research population were all students of X MIPA SMAN 1 Gunungsari that has 4 classes. Sampling technique of this research used purposive sampling conducted into two classes, they were X MIPA 1 as the experimental class and X MIPA 2 as the control class. Type test used 20 choice questions. The posttest mean value for concept mastery in experimental class and control class were 70,17 and 63,33. Hypothesis testing of this research used t test. The result of t test showed the value of thitung got 2,47. The value is bigger than ttabel got 2,00. So, the conclusion of this research H0 was rejected and Ha was accepted, meant that there was the effect of cooperative meaningful instructional design assisted by interactive multimedia for studentsÃ¢â¬â¢ physics concept mastery.